Spawning time of Acanthaster cf. solaris on the Great Barrier Reef inferred using qPCR quantification of embryos and larvae: do they know it’s Christmas? - Sven Uthicke; Eric E. Fisher; Frances Patel; Beatriz Diaz-Guijarro; Jason R. Doyle; Vanessa Messmer; Morgan S. Pratchett (Marine Biology, 2019)
Outbreaks of crown-of-thorns seastars (CoTS; Acanthaster spp.) are a major contributor to degradation of Indo-Pacific coral reefs. Understanding the dispersal and fate of planktonic life stages is crucial to understand and manage outbreaks, but visual detection of CoTS larvae is challenging. We apply a quantitative PCR (qPCR) assay to enumerate CoTS larvae in a 3-year time series of plankton samples from two reefs (Agincourt and Moore Reefs) on the Great Barrier Reef. Plankton surveys were complemented with settlement assays, and benthic surveys of juvenile and adult densities over time. Only one out of 109 plankton samples from Agincourt Reef had detectable CoTS mtDNA compared to 41 out of 575 samples from Moore Reef. This may be explained by differences in adult densities, or differences in connectivity and larval retention. Detections of larval CoTS were restricted to summer (November–February), with first detections each year coinciding with water temperatures reaching 28 °C and peak detections late December. A disproportionate number of larval detections occurred in 7 days around full moon. Complementary sampling of settlement and post-settlement life stages confirmed that elevated densities of CoTS larvae at Moore Reef translated to high rates of settlement adding to infestations at this reef. Moreover, there were declines in the detection of larvae, as well densities of juvenile and adult CoTS at Moore Reef, in 2017 and 2018. This study demonstrates that qPCR for genetic identification and quantification of larvae can assist to elucidate life history parameters of nuisance species difficult to obtain with other tools.